The Importance of Using Physical Tridimensional Models for the Management and Planning of Extended Osseous Odontogenic Lesions - Domenico Guerra; Marco Severino; Sara Caruso; Sofia Rastelli; Roberto Gatto (MDPI AG, 2021)
(1) Surgical intervention becomes crucial in situations in which lack of action would cause a decrease in quality of life for the patient. As healthcare professionals, our next objective is to reduce patient fear perception. This work's aim is to illustrate how physical tridimensional models can serve not only as confidence boosters for the patient, but also as a valid tool to aid both the clinician and the fostering of a patient-doctor relationship. (2) An example case managed using a stereolithographic model in the pre-surgical planning stage is presented in which surgical planning was carried out by analysis of radiographic investigations combined with a tridimensional resin model derived from the patient's x-ray exam. (3) Successful enucleation, surgical debridement, and stable follow-up shows the effectiveness of the applied surgical protocol, confirming that planification using a physical representation of the tridimensional exam aids in the correct surgical management of said lesions. (4) The effectiveness o101f the surgical act itself as well as the follow-up showing ossification of the bony lesion and absence of relapse of a highly recurrent lesion confirms the effectiveness of the tools used for this surgical intervention.